A performance analysis of scoring in professional boxing: Can it help? - Thomson, E. (The Sport and Exercise Scientist, 2012)
Clearly the current, albeit somewhat simplistic, analysis has highlighted the potential for employing PA to validate judges` scoring in professional boxing bouts. In the two examples scrutinised, the analysis of offensive actions served to both support the case made by one boxer (Khan) to challenge the outcome of his fight, and undermine that made by another (Pacquiáo) after his. Provided that the analysis issues of validity and reliability are satisfied, the ideas expressed herein may also be applicable to other sports in which less than objective judging decisions determine performance outcome. Given the increasing financial stakes in elite sport, the use of PA for corroborating judging decisions seems timely and is worthy of serious consideration by governing bodies of sports. It should be noted that a valid and reliable boxing analysis is unlikely to be accomplished in real-time owing to the speed of the actions performed and the occasional unfavourable orientation of the boxers (obstructing the view of the analyst, particularly if sitting ringside). Thus, PA could not be used to provide a rapid supplement to, or appraisal of, the existing judging system. Importantly, however, given that boxing governing bodies typically take several weeks to resolve an appeal, the type of scrutiny described in this article could be accomplished within that time and inform the outcome.